Problema Kesulitan Siswa Sekolah Dasar dalam Pembelajaran Geometri - Eka Rahayu (At- Ta'lim : Jurnal Pendidikan, 2021)
This study aims to find out how the difficulties that are often experienced by elementary school students in learning geometry. The research approach used is qualitative approach with descriptive research type. The subjects of this study were the teacher of Tunjung Sekar 2 School of Malang. Data collection techniques are done by interviewing teachers related to student difficulties and solutions that teacher do to overcome it. Data analysis was done by describing the interview result. The results of the study found that students have difficulties in multiplication and division, geometry and problem-shaped concepts. Actions undertaken by teachers to overcome student difficulties include learning is done by confronting students on concrete objects and make students experience themselves. In addition students are given enrichment for those who already understand and remidi for students who do not understand, cooperate with parents and before going to class in the morning held literacy and memorize multiplication. The average student's mathematical achievement has increased after several solutions have been applied.